Local Self Government-the Foundation of Democratic Political System - Jelena Trajkovska Hristovska (Iustinianus Primus Law Review, 2021)
Analyzing local self-government issues is particularly complex. Having in mind that local self-government is one complex and specific system of organization of powers on local level, its analysis should be done from different aspects, covering a large number of issues. Local self-government synthesizes a wealth of different systems, forms, normative solutions and principles. Hence this paper will determine and analyze the basic features of local self-government. This will enable the differentiation of the local self-government from the categories of decentralization and deconcentration. This paper also elaborates the system of local self-government in the Republic of North Macedonia, with special reference to the normative framework and the positive law, as well as the issues of local self-government authorities.
Keywords: Constitution, Local self-government, Deconcentration, Decentralization, Municipality, Local self-government Authorities, Municipal council, Mayor